The Influence of Outdoor Learning Method Towards Learning Outcomes and Interests - syarifatun niam alfiani (Berkala Ilmiah Pendidikan Fisika, 2020)
This study aims to analyze using outdoor learning methods on learning outcomes and interest in learning physics. This study uses a quasi-experimental method. This study involved 60 students from two classes, namely class XA and XB. The instruments used in this study were the pretest-posttest questions and the interest in learning questionnaire. Data analysis techniques used independent sample t-test, N-gain, and multivariate analysis of variance (MANOVA). The analysis results show that the treatment has a significant effect on learning outcomes and can improve learning outcomes compared to conventional learning. The outdoor learning method makes students more interested in learning physics. The conclusion that can be drawn is the outdoor learning method has a significant effect on learning outcomes and interest in learning physics in high school.